2011
DOI: 10.1088/0967-3334/32/9/009
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating a novel multi-sensor physical activity measurement system

Abstract: Advancing the field of physical activity (PA) monitoring requires the development of innovative multi-sensor measurement systems that are feasible in the free-living environment. The use of novel analytical techniques to combine and process these multiple sensor signals is equally important. This paper, describes a novel multi-sensor ‘Integrated PA Measurement System’ (IMS), the lab-based methodology used to calibrate the IMS, techniques used to predict multiple variables from the sensor signals, and proposes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…In addition, the thorough training and quality control procedures should have minimized coding errors. The sample sizes of the study cohorts were modest, although comparable to most studies of this sort (11,13,17,25,30,33). The total minutes and days of data collected, however, were much greater than previous studies.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, the thorough training and quality control procedures should have minimized coding errors. The sample sizes of the study cohorts were modest, although comparable to most studies of this sort (11,13,17,25,30,33). The total minutes and days of data collected, however, were much greater than previous studies.…”
Section: Discussionmentioning
confidence: 84%
“…Our algorithms performed similarly to algorithms developed using other machine learning or statistical techniques (11,13,17,25,30,33). Most previous studies have been conducted in laboratory settings (13), or with some observed data in outdoor locations (30).…”
Section: Discussionmentioning
confidence: 97%
“…[125][126][127]213 Several groups [128][129][130]159,214,215 have investigated how to extract and use more of the accelerometer signal using machinelearning algorithms to process data. These analyses provide detailed information about overall physical activity behavior, including time spent in different intensities of physical activity and activity type.…”
mentioning
confidence: 99%
“…The SVM converts the original features which usually are in a lower dimensional space to a higher dimensional space by using kernel functions such as a Gaussian radial basis function. Various studies have successfully applied ANN (52, 57) and SVM (33, 43, 53) for estimating PAEE, and promising results have been reported. For example, by applying an ANN model to signals from a biaxial accelerometer worn at hip, Rothney et al .…”
Section: Modeling Of Pa Energy Expenditurementioning
confidence: 99%